(3GdJUajI ddbdhH Yf cOQ GdChRGQ hGdPfhHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdeHOY GddWja GdNHjQ CeG HYO aEf GdebUhO HgPG GdEedGA gh GdETGQI Edi JUajI GdfahS Yf GdQPGFd , hJRcjI GdCNdGb hGdJMdi HeMGSf GdTeGFd , hJWgjQgG Yf GdChUGa GdQOjI s
(3BNQgG (B:s
(3hdfNJe cJGHfG gPG HGdEHJgGd Edi Gddg , hGdEYJPGQ Edjg , afbhd (B: (3Gddge EfG fSJZaQc ef LejY eG gLS ai GdCaFOI hGdNhGWQ s
(3HgG fXGe GdJYbjHIs
(3ai ChdgG HVY hQbGJ HNW MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdSjO eMeO Hf ESeGYjd GdeXgQ s
Keywords: (3GdJGQjNs